Flunarizine, Calcium Channel Blocker, Locally Improves Functional Recovery of the Transected Sciatic Nerve After Bridging With Inside-Out Vein Graft. Issue 4 (November 2016) - Mohammadi, Rahim; Alijanpour, Abolhasan; Alijanpour, Kamran; Hajili, Atefeh; Amini, Keyvan
Abstract : The objective was to assess the effect of locally administered flunarizine (FNZ) on transected peripheral nerve regeneration and functional recovery. Sixty male healthy white Wistar rats were divided into 4 experimental groups (n=15), randomly: in transected group, left sciatic nerve was transected and stumps were fixed in the adjacent muscle. In treatment group, defect was bridged using an inside-out vein graft (IOVG/FNZ) filled with 10 μL FNZ (100 ng/mL). In vein graft group (IOVG), the graft was filled with phosphate-buffered saline alone. In sham-operated group (SHAM), sciatic nerve was exposed and manipulated. Each group was subdivided into 3 subgroups of 5 animals each and regenerated nerve fibers were studied 4, 8, and 12 weeks after surgery. Behavioral testing, biomechanical studies, sciatic nerve functional study, electrophysiological, gastrocnemius muscle mass, and morphometric indices confirmed faster recovery of regenerated axons in IOVG/FNZ than IOVG group ( P <0.05). In immunohistochemistry, location of reactions to S-100 in IOVG/FNZ was clearly more positive than that in IOVG group. When loaded in a vein graft FNZ accelerated and improved functional recovery and morphometric indices of sciatic nerve. This may have clinical implications for the surgical management of patients after facial nerve transection.